Status and Decline of Amphibians of Afghanistan - Das, Indraneil (Natural History Publications (Borneo) Sdn. Bhd, 2014)
The Islamic Republic of Afghanistan (total land area: 547,500 km2 ) (Fig. 1) is a land-locked country in southern central Asia, bounded by the central Asian republics of Turkmenistan, Uzbekistan, and Tajikistan to the north, Pakistan in the east and south, China to the extreme northeast, and Iran on the west. Mostly arid, the landscape is dominated by the mountains of Hindu Kush, located on a northeast-southwest axis, a barrier to the dispersal of Indian elements from the south and west, and to the steppe faunas and floras of Turkmenistan, Uzbekistan, and Tajikistan, to the north and west.